DERMATOMIOSITIS: DERMATOMYOSITIS - ANDRE ANDRE (NEURONA, 2022)
Dermatomyositis is a rare idiopathic inflammatory myopathy disease. Inflammation in dermatomyositis causes muscle and skin damage. In this case report, a 42-year-old woman was diagnosed as dermatomyositis showing main symptoms of progressive weakness in both arms and legs, also rash on the skin. The diagnosis of dermatomyositis was made based on the criteria of the 239th European Neuromuscular Centre (ENMC) International Workshop 2018. The patient was given steroid and steroid-sparing agent as her primary management. Keywords: dermatomyositis, myopathy, rash, skin